Rotasi Dan Mutasi Terhadap Kinerja Karyawan Universitas Flores - Helena Carolinda Dua Mea, Maria (Catholic University Musi Charitas, 2022)
The goal of this study was to 1) determine the effect of rotation on the performance of University of Flores employees and 2) determine the effect of mutation on the performance of University of Flores employees. The sample size was 62 people, all of whom were permanent employees of the University of Flores. Questionnaires were distributed to gather data. SmartPLS Software is used to process data. The findings revealed that rotation had a positive (0.477>0) and significant (4.691>1.96) effect on employee performance at the University of Flores, while mutations had a positive (0.254>0) and significant (2.185>1.96) effect. Rotation and mutation influence the performance of University of Flores employees by up to 45 percent, with the remainder influenced by other variables not explained in this study.